The effect of Mentimeter on students’ Writing achievement in online learning - Ima Chusnul Chotimah; Dian Anik Cahyani (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
This study examines the use of Mentimeter on students’ writing descriptive text in online learning at Hasyim Asy'ari University Tebuireng Jombang. This study used a quantitative approach with a quasi-experimental design. The subjects in this study were Management class students which consists of twenty-two students as the experimental class and Elementary School Teacher Program class students which consist of seventeen students as the control class in English for Specific Purposes course. The research instrument is an essay test, which will be given before (Pre Test) the treatment to determine students’ prior knowledge and after (Post Test) treatment to determine the effect of using Mentimeter. After analyzing the data using Mann-Whitney U Test, the results showed that there was a significant difference in the mean rank of 23.59 on the use of Mentimeter and 13.35 on the use of power point. The statistical test obtained Asymp.Sig. (2-tailed) of 0.022, it is lower than the 0.05 level of significance. It means that the use of Mentimeter can influence students’ writing ability in online learning.DOI: 10.26905/enjourme.v7i1.7900